Blood cholesterol levels of hypercholesterolemic rat (Rattus norvegicus) after VCO treatment - MARTI HARINI; OKID PARAMA ASTIRIN (Nusantara Bioscience, 2009)
Abstract. Harini M, Astirin OP. 2009. Blood cholesterol levels of hypercholesterolemic rat (Rattus norvegicus) after VCO treatment. Nusantara Bioscience 1: 53-58. This study aims to determine the treatment effect of VCO on blood cholesterol levels in hypercholesterolemic white rats (Rattus norvegicus L.). This study used 25 male rats of Wistar strain divided into five treatment groups, namely: control, simvastatin (1.3 mL/270 g BW), cholesterol (9:1 lard), VCO 1 (1 mL/270 g BW), and VCO 2 (1.3 mL/270 g BW). Treatment was given orally. Total cholesterol, LDL, and HDL cholesterol levels were measured on days 1, day 14, and 28. Cholesterol data (total cholesterol, LDL, and HDL) were analyzed by ANOVA and followed by a contrast test at a significance level of 5%. The results showed that treatment of VCO at different doses significantly affected the decrease in blood total cholesterol blood LDL levels, increasing blood HDL in the hypercholesterolemic white rat.